How does being a medical student determine health promoting behaviors? - SAVE, DİLŞAD; BAYAR, ELİF SAMİYE; KAYA, GÜLİN; KARAVUŞ, MELDA (MARMARA UNIV, FAC MEDICINE, 2018)
Objectives: The aim of the study was to determine healthy lifestyle behaviors of the 1st and 6th grade students in a public medical school and the associated factors. Materials and Methods: Our descriptive study had included students from grades 1 and 6. Healthy Lifestyle Behavior Scale II (HLBS II) and a questionnaire for sociodemographic variables were completed by 213 students. Results: The mean age of participants was 21.6 +/- 2.5. 115 (54.0%) were male and 119 (55.9%) were in the first grade. The total mean score of HLBS II was found to be 128.61 +/- 16.54. No significant difference was found between the first and sixth year medical students (P>0.05). Subscale mean scores of spiritual development and interpersonal relationship for 6th grade students were higher than the scores of 1st grade students (P<0.05), whereas, average subscale scores of physical activity for 1st grade students were higher than the scores for 6th grade students (P<0.05). Conclusion: Healthy Lifestyle Behavior Scale II total score of the participants was slightly higher than moderate. In order to promote healthy lifestyle behavior, social programs for first grade students and intervention programs for physical activity for sixth grade students are needed.
Keywords: University students; Healthy lifestyle behavior; Health promotion; Medical students; UNIVERSITY-STUDENTS